(untitled) (Ágora de Heterodoxias, 2024)
Inaugural lecture by Dr. Victor Rago, Rector of the Universidad Central de Venezuela on the occasion of the opening of postgraduate courses of the Center for Development Studies (CENDES), academic year 2023